Narrativas transmedia y proximidad política en la campaña electoral de Jorge Yunda Machado, Alcaldía de Quito 2019 - Dra. María José ENRÍQUEZ CRUZ,Mgt. Juan Sebastián GÓMEZ NAVAS (Fonseca, Journal of Communication, 2023)
The study explores how transmedia storytelling was used to generate strategies of proximity in the municipal campaign of Jorge Yunda Machado to the Mayor of Quito 2019 elections, and how these conditioned the image of the candidate, as a «close and human» politician allowing an «anti-charismatic» identification toward the community of voters. For this a qualitative investigation was used, with content analysis (denotative and connotative) as a methodology for processing the information obtained from the media outlets and expert interviews